An analysis of the digital services tax solutions presented in Africa and early-adopting developed countries to inform South Africa on the design features for taxing the digital economy - Cupido, Sandy Deliah (Department of Finance and Tax, 2025)
South Africa has announced plans to adopt the Organisation for Economic Co-operation and Development's (“OECD”) Two-Pillar Approach and is currently preparing for Pillar Two's implementation, as the design and consensus for the implementation of Pillar One is progressing at a slower pace. While both pillars originated from the need to address Base Erosion and Profit Shifting (“BEPS”) issues, it is Pillar One that is primarily focused on taxing digital economy, whereas Pillar Two is focused on implementing a global minimum corporate tax rate. Thus, Pillar Two's implementation may not satisfy South Africa's need to tax the digital economy and generate revenue from the supply of digital services, in the manner that Pillar One is intended to. During this time, while the future of Pillar One unfolds, South Africa may find it useful to pause and consider alternative approaches to taxing the digital economy. Digital services tax (“DST”) has emerged as the most prevalent unilateral approach to taxing the digital economy, especially among African countries. In light of the issues regarding the global consensus required to implement Pillar One and the time it will take to get the United Nations (“UN”) Framework Convention on International Tax Cooperation underway, an opportunity exists for South Africa to consider implementing a DST to tax the digital economy and benefit from the additional tax revenue to be generated in the interim. Given the existing complexities in the South African tax system, a DST presents a simpler and more manageable approach to introduce to the South African tax landscape for the purpose of taxing the digital economy. Since a DST would be introduced unilaterally by South Africa, its design features could be tailored to meet the country's specific needs for taxing digital services. Accordingly, the primary research objective of this dissertation is to identify and analyse the DST design features that South Africa could consider if a DST was to be implemented as an alternative approach to taxing the digital economy. The primary research objective is addressed by sub objectives that comprise of: discussing potential benefits and challenges of implementing DSTs, analysing the DSTs of early-adopting developed countries that were among the first to implement DSTs, by identifying key commonalities in the design features; analysing the DST legislation of the African countries that have implemented DSTs, by identifying and examining similarities and variations in the design features; and analysing the design features of the African Tax Administration Forum's (“ATAF”) Suggested Approach to Drafting Digital Services Tax Legislation (“ATAF's Suggested Approach”) with those of the African DSTs, to identify areas of alignment or deviation. ABSTRACT 4 The dissertation provides a comprehensive list of potential benefits and challenges of DSTs to assist South Africa in weighing up the positives and negatives of implementing a DST to tax the digital economy. From the further analyses performed, it is concluded among other findings, that similarities exist between the design features of the DST solutions as it pertains to the tax base, scope of digital services and minimum DST thresholds, while variations are identified in the design features regarding source rules and determining user participation. These shared trends are further interpreted to provide insights into how the DST design features could be considered by South Africa.